Gallstone ileus: the importance of individualized management - Enrique, Soulé-Martínez Christian; David, Alfaro-Ponce; Leonel, Castellanos-Aguilar; Michel, Jaimes-Durán Edwing; Rodrigo, Banegas-Ruíz; Angel, Barajas-Colón Jose; Issac, Valderrama-Treviño Alan (International Surgery Journal, 2021)
Gallstone ileus represents a complication of cholelithiasis, which in the literature has been reported as a rare cause of mechanical intestinal obstruction, however, the reported incidence is not so low, especially after 65 years of age. The formation of a bilioenteric fistula allows the passage of a large gallstone into the intestine, usually impacting the distal intestine. It is associated with a mortality that ranges between 12 and 27%. Treatment is surgical, although there is no consensus on which of the surgical techniques is the one of choice. We report the case of an 87-year-old male patient who was admitted to the emergency department with intestinal obstruction. He was diagnosed with gallstone ileus and was treated surgically with exploratory laparotomy, enterotomy with stone extraction, and primary closure. The evolution was favorable and without complications.